IMPUTATION OF CRIMINAL RESPONSIBILITY IN THE CRIME OF MONEY LAUNDERING - Rudá, Antonio Sanches Sólon (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
This work aims to address the incrimination of the reckless modality and the requirement of an exhaustive list of predicate offenses in the crime of money laundering in Portugal, Spain and Brazil. Focusing on the imputation of criminal responsibility for this type of crime, the research aims to critically analyze the legislative and jurisprudential aspects of each of these institutes, with the aim of understanding to what extent the systematic adoption of one or the other can influence the issue. of the effectiveness and dignity of criminal law